Analysis On Court Decision No 147/Pid.B/2022/Pn Denpasar On Notary Liability In Adopting Minutes Of Extraordinary General Meeting Based On Circular Resolutions Inconsistent With Actual Facts - Adi Kusuma, Hanif; Hartiwiningsih, Hartiwiningsih; Dyah Kusumawati, Erna (CV. Inara, 2024)
The Purpose Of This Research Is To Analyze And Examine The Accountability Of A Notary As The Creator Of The Minutes Of An Extraordinary General Meeting Of Shareholders Based On A Circular Decision That Does Not Reflect The Actual Facts. The Type Of Research Used In This Study Is Normative Legal Research. The Research Conducted By The Author Is Prescriptive In Nature. The Approaches Used In This Research Are The Statutory Approach And The Case Approach. The Types Of Legal Materials Used In This Study Are Primary Legal Materials And Secondary Legal Materials. In An Effort To Find And Collect The Necessary Data, This Research Uses The Technique Of Collecting Library Research Or Document Study. The Analysis Technique Used In This Research Is The Syllogism Method Using Deductive Thinking Patterns. The Results Of This Research Indicate That The Accountability Of A Notary As The Creator Of The Minutes Of An Extraordinary General Meeting Of Shareholders Based On A Circular Decision That Does Not Reflect The Actual Facts Can Be Qualified As An Unlawful Act Due To Negligence As Regulated In Article 1365 Of The Civil Code, Which Regulates The Notary's Civil Liability Or Sanctions Against The Notary To Compensate For The Losses Suffered By The Disputing Parties Due To Such Unlawful Acts. Based On This, The Accountability Of The Notary Who Has Been Convicted For Violating The Provisions Of Article 264 Paragraph (1) In Conjunction With Article 55 Paragraph (1) Number 1 Of The Criminal Code In The Making Of The Minutes Of The Egm Also Constitutes Administrative Violations For Violating The Obligations Of A Notary In Carrying Out His Duties And Responsibilities As Regulated In Article 16 Paragraph (1) Letter A Of The Notary Law As Well As Violating The Notary Code Of Ethics Article 3 Paragraph (2), (3), (4).